Eliminating the role of the minister in representation for unfair dismissal claims to industrial court - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (Lexis Nexis Malaysian Sdn Bhd, 2018)
This article discusses the issue whether the Minister should cease to be a conduit to refer cases of unfair dismissal to the Industrial Court.